Karakterisasi Sifat Agronomi Tanaman Padi Beras Merah Dihaploid Berpotensi Hasil Tinggi Diperoleh melalui Kultur Antera Antera - ,, Mawaddah; Purwoko, Bambang Sapta; Dewi, Iswari Saraswati; Wirnas, dan Desta (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2018)
Observation and identification of rice germplasm with advanced traits are important activities in the process of obtaining a variety of rice because every genotype will show unique characters. Genotype derived from breeding program as anther culture need to be characterized to identify the doubled haploid lines that are potential to be developed in red rice breeding. This research was aimed to obtain agronomic characters of doubled haploid lines of red rice. Materials used were 59 genotypes, i.e., 57 doubled haploid (DH0) lines with red grain and 2 check varieties (Inpari 24 and Aek Sibundong) as control. The experiment used a randomized complete block design with three replications. The results exhibited there was agronomic variation among DH0 of red rice lines. Variance analysis showed that genotype affected most characters, except for grain dry weight per hill. Plant height, number of productive tiller, harvesting age, panicle length, number of grains per panicle, and number of filled grain per panicle can be used as a reference for effective selection to develop high productivity of red rice variety.